Pelatihan Aplikasi Program SPSS Bagi Dosen Fakultas MIPA Universitas Kristen Indonesia Tomohon: SPSS Program Training for Faculty of Mathematics and Natural Sciences Lecturers, Universitas Kristen Indonesia Tomohon - Kekenusa, John Socrates; Hatidja, Djoni; Paendong, Marline S. (Vivabio: Jurnal Pengabdian Multidisiplin, 2025)
SPSS Program Application Training for FMIPA Lecturers at the Indonesian Christian University Tomohon was carried out according to the requests and needs of the participants. The knowledge qualification of lecturers about data analysis using computer applications is still relatively low, so it needs to be improved. This training aims to improve the knowledge and skills of the participants about statistics, especially about data analysis using SPSS computer software. With the facilitation of a guidebook and direct practice, the trainees can do data input, data description, and interpretation of data analysis results.  Participants perform independent tasks about data input, data description, and interpretation of data analysis results. Participants also reported the results of their independent work well. According to the results of the evaluation, all participants can practice the use of SPSS in conducting data analysis, as well as draw conclusions from the results of the data analysis. The benefit of this activity is that the participants gain broader knowledge and insight about statistics, especially research data analysis.  Trainees better understand data analysis using the SPSS application, so that it can improve the quality of research and teaching. ABSTRAK          Pelatihan Aplikasi Program SPSS Bagi Dosen FMIPA Universitas Kristen Indonesia Tomohon  dilaksanakan sesuai permintaan dan kebutuhan peserta. Kualifikasi pengetahuan para dosen tentang analisis data menggunakan aplikasi komputer masih relatif rendah, sehingga perlu ditingkatkan. Pelatihan ini bertujuan untuk meningkatkan pengetahuan dan ketrampilan para peserta tentang statistika, khususnya tentang analisis data menggunakan software komputer SPSS.. Dengan difasilitasi buku panduan serta praktek langsung, para peserta pelatihan dapat melakukan cara input data, deskripsi data, interpretasi hasil analisis data.  Peserta melakukan tugas mandiri tentang input data, deskripsi data, serta interpretasi hasil analisis data. Peserta juga melaporkan hasil kerja mandirinya dengan baik. Sesuai hasil evaluasi, semua peserta dapat mempraktekknn penggunaan SPSS dalam melakukan analisis data, serta menarik simpulan hasil analisis data tersebut  Manfaat kegiatan ini ialah para peserta mempeoleh pengetahuan dan wawasan yang lebih luas tentang statistika khususnya analisis data penelitian.  Peserta pelatihan lebih memahami analisis data menggunakan aplikasi SPSS, sehingga dapat meningkatkan kualitas penelitian dan pengajaran.